An Analytical Study of Relationship Values Between Parents and Children in Buddhism - (ศรีจันทร์), พระนัฐวุฒิ สิริจนฺโท, ผู้ช่วยศาสตราจารย์ ดร., พระครูสุธีคัมภีรญาณ; บัวระภา, ผู้ช่วยศาสตราจารย์ ดร.หอมหวล (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
This article aims to study the analytically study the relationship values between parents and children in Buddhism. As In the society, human beings live together and rely on one another, help each other so that they can live and be safe. Human beings communicate to obtain the behavioral understanding through languages and acting for building good relationship and mutual friendship. Particularly, the relationship between parents and children is very important because the family is recognized as the base of the society. All family members must have a good mutual relationship. Parents must teach their children to avoid bad conducts, behave good-deeds, be educated, find a good spouse and give them wealth in proper occasions. On the other hands, children must take care of their parents, help them to work, behave properly as their heirs, after their parental passing away, they should perform meritorious deeds to dedicate merit to them. The family is the basic institute to develop the country. If this institute is weak and unstable, the nation will confront with the problems. If it is strong, it will affect the society as a whole. If the family members do their duties in teaching each other, train them to have a good personality, behaviors, morals, being a good citizen, correct communication, this will support the development of the country.